Cyclooxygenase-2 and β-Catenin as Potential Diagnostic and Prognostic Markers in Endometrial Cancer - Deng, Lin; Liang, Haiyan; Han, Yi (Frontiers in Oncology, 2020)
Objectives: To evaluate the diagnostic and prognostic potential of cyclooxygenase-2 and wnt3a/β-catenin pathway in patients with endometrial cancer. Methods: Prospective case control study of 111 women who underwent hysterectomy at the China-Japan Friendship Hospital (67 patients with primary endometrial carcinoma, 44 control patients with uterine prolapse or leiomyoma of uterus). Expression of cox2 and β-catenin were determined by immunohistochemistry. The levels of cox2 and wnt3a were detected via ELISA assays. Results: Patients with endometrial cancer showed overexpression of cox2 and β-catenin, as well as significantly higher serum levels of cox2 and wnt3a. All markers were positively correlated with tumor clinicopathological parameters and could be used for stratifying patients according to deep myometrial invasion, lymph node metastasis and vessel invasion. Serum cox2 and wnt3a levels showing good diagnostic and prognostic potential with cut-off of 50.22 U/L, 20.37ng/ml, respectively. All markers were related to poor prognosis, and serum cox2 level is the most significant one predicting the risk of disease progressing (HR, 4.204, 95% confidence interval, 1.468-12.041, p=0.007). Conclusion: Logistic regression models based on the serum levels of cox2 and wnt3a exhibited good diagnostic accuracy for separation of patients with endometrial cancer from control patients. Among patients with endometrial cancer, cox2 serum levels showed significant prediction of poor prognosis based on cox regression models. Cox2 serum levels could be a marker for early diagnosis and prognosis prediction of patients with endometrial cancer.